Development of a computerized aid to integrated land use planning (CAILUP) at regional level in irrigated areas : - Chu, Thai Hoanh (International Institute for Aerospace Survey and Earth Sciences, 1996)
This study develops and implements a method and corresponding software system for integrated land use planning at regional level in irrigated areas, and to test the method and the system in the Quan Lo Phung Hiep region in the Mekong Delta, Vietnam. The System Development Methodology (SDM) comprising seven specific phases was applied in the study. A Computerized Aid to Integrated Land Use Planning, "CAILUP", was formulated